Elizabeth : the forgotten years - Guy, J. A. (John Alexander) (United Kingdom : Viking, 2016)
A groundbreaking biography of Elizabeth I revealing for the first time the woman behind the polished veneer as she confronts challenges at home and abroad: war against the Catholic powers of France and Spain, revolt in Ireland, an economic crisis that triggered riots in the streets of London, and a conspiracy to place her cousin Mary Queen of Scots on her throne.
Introduction: A virgin queen -- A city in fear -- Crisis and betrayal -- Brave new world -- Armada of the soul -- No warrior queen -- A funeral and a wedding -- On the attack -- The visible queen -- The enemy within -- Catastrophe in France -- "Good Queen Bess" -- The quest for gold -- Conspiring against the queen -- Games of thrones -- A counter-armada -- One last chance -- Seeking détente -- Opening new fronts -- Defying the queen -- "I am Richard II" -- The queen's speech -- On a knife's edge -- The final vigil.
Includes bibliographical references and index.
Keywords: Elizabeth -- I, -- Queen of England, -- 1533-1603.; Elizabeth -- I, -- Queen of England, -- 1533-1603.; 1558-1603; Queens -- Great Britain -- Biography; Queens; Great Britain -- History -- Elizabeth, 1558-1603.; Great Britain; Biographies; Biography; History; Biographies